Deskripsi Perkembangan Keterampilan Dasar Kerja Laboratorium Kimia Siswa SMA Negeri 1 Singaraja - Kartini, Ketut Sepdyana (IKIP Mataram, 2018)
The aims of this study was to describe the development of basic skills students in achemistry laboratory carrying out the work. This study was conducted using a qualitative approachwith the subject of the research is 603 students consisting of 8 classes of X grade, 7 classes of XIgrade and 7 classes of XII grade. Data were collected with observation papers. The results showedonly 8 out of 10 aspects of the basic skills of laboratory work were observed. Five aspects of skillsclassified into very well categories and three categories of skills aspect quite well.